PERILAKU ‘LOMPAT PAGAR’ POLITISI MENJELANG PEMILU LEGISLATIF 2014 DI JAWA TENGAH - Shabrina Hana Mutiara Negara; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2020)
The 2014 legislative elections have been marked by the transfer of party cadres to otherparties. This phenomenon is like that carried out by a number of parties in Central Java. Fromthe data search, there is no exact value of the number of cadres who carry out the partymovement in question. But from the writer's search there were two cadres, the first being Drs.Fadholi, he was elected as a Member of the House of Representatives of the 2014-2019 periodfrom the Democratic National Party (Nasdem). Next, Nur Hadi was originally a cadre of thePKNU, moving to the PPP Pekalongan City.This research is a field research with descriptive qualitative research methods that aredescriptive and tend to use analysis with an inductive approach. In data retrieval carried out byusing the method of in-depth interviews and documentation. Interviews were conducted at theresidence of the two informants in Salatiga City and Pekalongan City.The results of the research show that the phenomenon of politicians moving parties inPekalongan Regency and Salatiga City is a normal political reality in the Indonesian politicalarena, due to the many motives of politicians. The rise of politicians moving parties ismotivated by the blurred ideology of political parties, the failure of political parties inconducting political education, and ineffective cadre system. Political parties are not wellestablished in the function of regeneration so that cadres in their political activities do notanimate party ideology, thus leading to political pragmatism by politicians. In addition to themotives of pragmatism, it is also known that there are motives so that politicians can maintaintheir existence in elections by moving parties.The suggestion from the author is the need for a comprehensive revitalization of politicalparties in their political activities, political parties must restore their struggle as a bridge inconveying people's aspirations.Keywords: Political Behavior, Legislative Elections 2014